The cooling of naphthalene cations studied within an electrostatic storage ring. (29th January 2015) - Ortéga, C; Brédy, R; Chen, L; Bernard, J; Ji, M; Montagne, G; Allouche, A R; Cassimi, A; Joblin, C; Martin, S
Abstract: Fast population decay of naphthalene cations (C10 H8 + ) has been observed in a compact electrostatic storage ring, the Mini-Ring, up to 5 ms. Laser induced dissociation due to single-photon absorption was used to probe the internal energy distribution (IED) of the stored molecular ions as a function of the storage time. To determine the energy distribution of naphthalene cations, the experimental neutral decay curve was analysed with a model including the competition between dissociation and radiative cooling. Fast cooling rates from about 70 s −1 at the internal energy 5.6 eV to 140 s −1 at 6.2 eV were measured and compared with the data in the literature. This fast cooling mechanism is attributed to the fluorescence from thermally excited electrons and may have important implications in astrophysics for the lifetime and the critical size of Polycyclic Aromatic Hydrocarbons (PAH) in the interstellar medium.